Preparation of hexakis (4‐aldehyde phenoxy) cyclotriphosphazene grafted kaolinite and its synergistic fire resistance in poly (butylene succinate). Issue 3 (15th November 2019) - Zhang, Sheng; Li, Yuchun; Guo, Jia; Gu, Lingling; Li, Hongfei; Fei, Bin; Sun, Jun; Gu, Xiaoyu
Abstract: Hexakis (4‐aldehyde phenoxy) cyclotriphosphazene (HAPCP) was synthesized firstly and then it was grafted onto the exfoliated kaolinite (Kaol) to prepare K‐HAPCP. The structure of HAPCP and K‐HAPCP was well characterized. K‐HAPCP was used as synergistic agent in poly (butylene succinate) (PBS)/intumescent flame retardants (IFR) composites. The combustion behavior of PBS composites was reflected by limited oxygen index (LOI), vertical burning (UL‐94), and cone calorimeter test. The thermal stability was traced by thermogravimetric analysis. PBS is highly flammable with the LOI value of only 21.9% and cannot pass any UL‐94 grade during vertical burning test. By the presence of 22 wt% IFR and 3 wt% K‐HAPCP, the LOI of PBS composite is sharply increased to 40.3% and the sample can pass UL‐94 V‐0 rating with excellent anti‐dripping properties. Moreover, the degradation behavior is investigated and the probable flame retardant mechanism is also proposed.